Climate warming increases biological control agent impact on a non‐target species. (7th November 2014) - Lu, Xinmin; Siemann, Evan; He, Minyan; Wei, Hui; Shao, Xu; Ding, Jianqing; Eubanks, Micky
Abstract Climate change may shift interactions of invasive plants, herbivorous insects and native plants, potentially affecting biological control efficacy and non‐target effects on native species. Here, we show how climate warming affects impacts of a multivoltine introduced biocontrol beetle on the non‐target native plant Alternanthera sessilis in China. In field surveys across a latitudinal gradient covering their full distributions, we found beetle damage on A. sessilis increased with rising temperature and plant life history changed from perennial to annual. Experiments showed that elevated temperature changed plant life history and increased insect overwintering, damage and impacts on seedling recruitment. These results suggest that warming can shift phenologies, increase non‐target effect magnitude and increase non‐target effect occurrence by beetle range expansion to additional areas where A. sessilis occurs. This study highlights the importance of understanding how climate change affects species interactions for future biological control of invasive species and conservation of native species.